Consumer Satisfaction In Retail Banking In Malaysia : An Importance Performance Analysis - Ho, Tan Swee (2001)
The main aim of this paper is to identify what the consumer wants from their bank and to investigate if the bank has delivered or fulfilled their wants thus far. It is a descriptive research that provides the banks with a sample of consumers' opinion of the level of importance in their expectation and satisfaction towards the banks along with the degree of performance of how the banks have fulfilled these expectations and met customer satisfaction.